Using UI - Dayal, Rajeev (Addison-Wesley, 2007)
"So, you've heard about the Google Web Toolkit, but you've been wondering if it can make your application's UI look rich and fluid like some of the other toolkits you've heard about ... Well, you've come to the right place! In this talk, we will take a look at some examples of slick user interfaces and demonstrate how to build them with GWT's UI library. Along the way, you'll learn about all of the different UI features that GWT has to offer."--Resource description page